Perlindungan Hukum Terhadap Lahan Pertanian Akibat Terjadinya Alih Fungsi Lahan di Indonesia - Ayu, Isdiyana Kusuma; Heriawanto, Benny Krestian (JU-ke: Jurnal Ketahanan Pangan, 2018)
Depletion of agricultural land the food also caused Indonesia to import food to meet the needs of the community. It should, with a vast territory, Indonesia can press the pace of food imports in order to capitalize on domestic products. However, this could not be realized because of the vast agricultural land are getting increasingly narrows because of the transition functions of land either for personal interest or the public interest. Based on the description of the need for further study of the question of the form the form related to the transition of the function of the agricultural land in Indonesia, a form of legal protection of agricultural land due to the occurrence of land in Indonesia over the function. This research was conducted with the normative method. Over the function of land can occur due to the procurement of land development to public interest and the transition is done by the owner to be non-agriculture. Act 41 the year 2009 has been protecting agricultural land with sustainable food there can be no transitional function except for the public interest and the existence of land his successor. A permit must be made by the owner of agricultural land when the land will divert his farm.